PROSES BERPIKIR MAHASISWAMATEMATIKA IKIP MATARAM DALAM PEMBUKTIAN KETERBAGIAN BERDASARKAN TEORI PEMROSESAN INFORMASI - JULIANGKARY, ELISKA; YUWONO, IPUNG; SULIANDRA, I MADE (IKIP Mataram, 2013)
Knuth (2002), Healey and Hoyles (2000) have studied on teachers and students? concept on prooving. However, those studies did not yet discover on case ?how does student?s thinking process on fragmentation proofing?.?The Information Processing Theory is one of the theories that focus on one?s thinking process. It is one of the members of cognitive learning type theory which digs detail and deep on the relationship between subdivisions of information since it has been received from its surrounding until it permanently saved in someone?s mind. The aim of this study was describing thinking process of ikip mataram students in mathematic prooving based on information processing theory.